(±)-hyperzewalsins A−D, four pairs of nor-monocyclic polyprenylated acylphloroglucinols with immunosuppressive activity from hypericum przewalskii maxim. (July 2021) - Duan, Yulin; Bu, Pengfei; Xie, Shuangshuang; Guo, Yi; Shi, Zhengyi; Qi, Changxing; Zhang, Yonghui
Abstract: Three pairs of previously undescribed 2, 3-nor-monocyclic polyprenylated acylphloroglucinols (MPAPs), (±)-hyperzewalsins A−C, a pair of 1, 2, 3, 4-nor-MPAPs, (±)-hyperzewalsins D, along with one undescribed precursor, hyperzewalsin E, were isolated and identified from the aerial parts of Hypericum przewalskii Maxim. (Hypericaceae), and their structures were confirmed by extensive spectroscopic analyses, and quantum-chemical calculations including electronic circular dichroism calculations and NMR calculations with a DP4+ analysis. Significantly, (±)-hyperzewalsins A−D represented the first nor-MPAPs bearing carbon chain constitutions based on diverse highly degraded phloroglucinols. (±)-Hyperzewalsins A−C were the rare nor-MPAPs characterized by degradations of C-2 and C-3 in the core decorated by scissions of C-3/C-4 and C-1/C-2 bonds through Retro-Claisen reactions. (±)-Hyperzewalsins D were the first examples of naturally occurring MPAPs with the loss of C-1/2/3/4 in the phloroglucinol ring formed by cleavages of C-3/C-4 and C-1/C-6 bonds via Retro-Claisen and decarboxylation reactions. Plausible biogenetic pathways for the isolates were proposed. The isolates were evaluated for their immunosuppressive activity in lipopolysaccharide-stimulated murine splenocytes. Graphical abstract: Image 1 Highlights: Four pairs of previously undescribed nor-MPAPs were identified from Hypericum przewalskii Maxim. (±)-Hyperzewalsins A−D were the first MPAPs bearing carbon chain constitutions based on the degraded phloroglucinols. (±)-Hyperzewalsins B showed immunosuppressive activities in lipopolysaccharide (LPS)-stimulated murine splenocytes.